THU0154 Associations of Osteoporotic Fracture Genes in Patients with Rheumatoid Arthritis. (9th June 2015) - Rantapää-Dahlqvist, S.; Wiberg, K.; Ärlestig, L.; Pettersson, U.
Abstract : Background: Patients with rheumatoid arthritis (RA) have increased development of osteoporosis. We have identified an increased incidence of low-energy fractures in RA patients by analysing a population based register of fractures in northern Sweden. In RA increased serum levels and associations with genes encoding proteins involved in the Wnt pathway have been found and related to joint destruction in RA Objectives: To analyse in patients with RA nine SNPs related to osteoporotic fractures in the general population and to joint destruction in RA. Methods: The register of patients with RA (ARA criteria) consecutively included since 1995 (n=1178) was co-analysed with the register of Umeå injury database, Umeå, Sweden to identify low-energy fractures. This database was constituted in 1993 and covers six communities with a population at risk of 118000 adults. All individuals admitted to the emergency ward are included. DNA was available from 866 RA patients of whom 244 had a fracture after the diagnosis of RA. As controls served 997 sex and age matched population controls from the same area. The following SNPs have been analysed; rs3801387 (WNT16), rs6666455 (SOAT), rs3736228 (LRP5), rs4796995 (FAM210A), rs4792909 (SOST), rs2062377 (TNFRSF11B/OPG), rs884205 (TNFRSF11A/RANK), rs9533090 (TNFSF11/RANKl), and rs1373004 (DKK1) using KASP™ genotyping assays (LGC genomics Ltd, Hoddesdon, UK). Results: The distribution of the genotypes of rs4796995, rs3801387, and rs6666455 were not in Hardy-Weinberg equilibrium in the RA patients. Carrier of the major allele of rs4796995 was significantly associated with RA (odds ratio 1.48 [95%CI 1.06-2.06] p=0.020), and more strengthened among women (OR 1.62 [95%CI 1.10-2.39] p=0.014). The genotype distribution of rs1373004 differed significantly between RA patients with fractures and population controls (c 2 =8.21, p=0.017, 2df). Carrier of the rare allele was more common among RA patients with fractures compared with controls (OR 1.56 [95%CI 1.13-2.16] p=0.007). A difference in genotype distribution for rs4792909 (encoding sclerostin) was found comparing RA patients with and without fracture (c 2 =6.66, p=0.036, 2df). Being homozygous for the major allele was more common among those patients with fracture (OR 1.42 [95%CI 1.05-1.93] p=0.023) and after adjustment for ACPA, OR=1.51 [95%CI1.09-2.08] (p=0.012). Conclusions: Genes related to osteoporotic fractures in the general populations were identified also associated with increased risk of fractures in patients with RA. The increased risk of fracture in patients with RA has besides the disease and its treatment also a contribution of genetic factors suggested to be related to joint destruction. References: Estrada K et al Nat Genet 2012;44:491-501. Rooy de DPC et al Ann Rheum Dis 2013;72:769. Acknowledgements: The register of Umeå injury database, Umeå, Sweden and the Medical Biobank of northern Sweden. Disclosure of Interest: None declared